Bibliometrix Application on Halal Tourism Management Research - Sabiq Al Qital (SMART Insight, 2022)
This research aims to find out and map research related to the development of Halal Tourism Management research trends published by leading journals on Halal Tourism Management policy. The analysis focused on describing the characteristics and trends of the keywords, authors, and journals. The data analyzed were from 191 research publications in Scopus. The search terms were “Halal Tourism Management”. The searches used to establish the study dataset were last updated on May 11, 2022. Descriptive statistical methods were used, and a bibliometric analysis was conducted using Biblioshiny, an R-based app, to generate a bibliometric map. This study has found that the basic themes of this topic are